Circularity by stock in Sri Lanka: Economic necessity meets urban fabric renovation - Pathiraja, Milinda; Tombesi, Paolo (Frontiers in Built Environment, 2023)
Persistent fiscal and political mismanagement and the financial pressures of the COVID-19 pandemic have driven Sri Lanka into a social and economic crisis triggering a decrease in national foreign exchange reserves, an inability to purchase vital imports, and an unprecedented rise in internal inflation rates. Within the construction sector, the idea of 'design circularity' gains natural impetus as a critical strategy for responding to the material scarcity of the country’s by-now relatively closed economy. This is also in light of the fact that the post-independence history of industrial policy in the island has produced an urban landscape characterised by large underused, increasingly derelict building stock with significant potential - and need - to be programmatically reorganised, technically recycled, and spatially and culturally re-designed. This paper moves from the proposition that, for 'circularity' to be of use at the scale required, its design application must expand beyond conventional interpretations of material recycling, to acknowledge the overall building fabric as a critical, transformative resource available to be renewed or reborn, with varying degrees of reforms as called by the existing opportunities, underlying programmatic needs, and/or industrial constraints. In facilitating this function, architectural design has an important role to play, as particular sets of design strategies must be employed to handle the inevitable complexities between structure and form, material and content, and product and process, against a reflective understanding of local building logic, challenges and potential. To that end, professional design can help foster design approaches to resolve the technical intricacies of building fabric transformations, strategise actions concerning work procurement and economic planning, and provide the leading agency in setting up future-industry configurations. How this approach could inform and affect broad market notions of design circularity for Sri Lanka is evaluated through the review of three projects that focus on different programmatic transformations (residential-to-residential, residential-to-recreational, and commercial-to-recreational), are set within different geographical locales (city, periphery and in-between), and situated in and around Kandy, Sri Lanka’s second-largest city. The projects illustrate possible tactics for intervening on the existing fabric whilst considering the benefits of each and articulating the structural challenges for the practices involved.